The Influence of Earning Per Share and Proceed To Initial Return On Companies That Listed At Indonesian Stock Exchange That Make IPO of 2010-2013. - Dea Arsika; Ati Sumiati (Fakultas Ekonomi, Universitas Negeri Jakarta, 2015)
The purpose of this research was to study the significant effect of Earning Per Share and Proceed to Initial Return on Listed Companies in Indonesia Stock Exchange in 2010-2013. The method used is quantitative descriptive survey method with a descriptive and statistical analysis and regression approach. This research using the secondary data obtained from the reference center Indonesia Stock Exchange in 2009-2012, Elektronik Bursa and IPOT Indonesia. Variable X as the independent variabel is Earning Per Share and Proceed. Meanwhile variable Y isInitial Return. The sampling technique was conducted by random sampling. The attainable population in this research were all companies listed on the Indonesia Stock Exchange conducting IPO in 2010-2013 and the sample used by the table Isaac and Michael is 78 companies. The multiple linier regression and resulted Ŷ = 0.296 – 0.001X1 – 8.550X2. The result of this research concluded that Earning Per Share has negative significant where Thitung of Earning Per Share is -2.782 greater than Ttabel amounted to -1.665 and Proceed has negative and significant effect on Proceed where Thitung is -2.402 and Ttabel amounted to -1.665. In Simultan, The Influence Between Earning Per Share and Proceed with Initial Return is significantly related. The ability of Earning Per Share and Proceed explain Initial Return is 37,5%.